2009
DOI: 10.1159/000233246
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Overload-induced Right Ventricular Failure is Associated with Re-expression of Myocardial Tenascin-C and Elevated Plasma Tenascin-C Levels

Abstract: Background: We investigated whether (1) monocrotaline(MCT)-induced right ventricular (RV) dilatation is associated with re-expression of myocardial tenascin-C (TNC), (2) elevated plasma TNC levels can be used as a marker of ventricular dilatation, and (3) MCT-induced RV dilatation is associated with alterations of other remodeling-related proteins. Methods: Rats were treated with MCT in low dose (30 mg/kg, MCT30, n=10) to induce compensated RV hypertrophy, in high dose (80 mg/kg, MCT80, n=11) to induce RV fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…As with the previous reports, we confirmed that MCT induced pulmonary hypertension, RV hypertrophy and dysfunction, all of which worsened over time [11]. In hypertrophied left ventricles of various cardiac disease animal models, such as angiotensin II (Ang II)-induced and transverse aortic constriction (TAC)-induced cardiac hypertrophy model mice, expression of SPARC, TnC, TSP-1, 2 and 4, CCN1 and 5, periostin and OPN was upregulated [1, 4, 9, 10, 15, 23, 25, 30, 32, 33]. SPARC family proteins play a role in processing of procollagen to mature collagens and in collagen fibril assembly [3, 4, 27].…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…As with the previous reports, we confirmed that MCT induced pulmonary hypertension, RV hypertrophy and dysfunction, all of which worsened over time [11]. In hypertrophied left ventricles of various cardiac disease animal models, such as angiotensin II (Ang II)-induced and transverse aortic constriction (TAC)-induced cardiac hypertrophy model mice, expression of SPARC, TnC, TSP-1, 2 and 4, CCN1 and 5, periostin and OPN was upregulated [1, 4, 9, 10, 15, 23, 25, 30, 32, 33]. SPARC family proteins play a role in processing of procollagen to mature collagens and in collagen fibril assembly [3, 4, 27].…”
Section: Discussionsupporting
confidence: 56%
“…Hessel et al . reported that TnC expression was increased in RV from high dose (80 mg/kg, 4 weeks) MCT-treated rats [9]. They suggested that TnC caused cardiomyocyte slippage followed by RV dilatation through de-adhesive activity and integrin β6 downregulation [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations